Two-site silica supported Fe/Cr catalysts for tailoring bimodal polyethylenes with variable content of UHMWPE - Kurek, Alexander Gerhard; Mark, Stefan; Enders, Markus; Stürzel, Markus Roland; Mülhaupt, Rolf (Journal of molecular catalysis. A, Chemical, 2014)
A new family of silica supported two-site Fe/Cr catalysts were prepared by means of sequential and simultaneous immobilization (“cosupporting”) of both 2,6-bis-[1-(2,6-dimethylphenyliminio)ethyl]pyridine iron(II) chloride (Fe) and η5-[3,4,5-trimethyl-1-(8-quinolyl)-2-trimethyl-silylcyclopentadienyl]chromium(III) chloride (Cr) on MAO-pretreated silica. The influence of catalyst preparation, catalyst composition, and of Fe/Cr molar ratio on catalyst activity, polyethylene (PE) molecular weight (MW), and PE molecular weight distribution (MWD), as determined by high temperature size exclusion chromatography, was examined. Catalyst activity increased with decreasing transition metal content. The average molar masses of the two PE fractions, UHMWPE (3×106g/mol), produced on Cr sites, and PE (3×105g/mol), produced on Fe sites, are independent of the Fe/Cr molar ratio. The sequential immobilization of the Fe complex prior to the Cr complex affords the highest catalyst activities and highest UHMWPE contents. Here, the UHMWPE content consequently increases from 0 to 32wt% with increasing Cr content at constant Fe concentration.
Online 24 November 2013
Gesehen am 16.09.2020